Value of a preoperative prognostic nutritional index for the prognostic evaluation of gastric neuroendocrine carcinoma patients - Wei, Jiangpeng; Lu, Ju; Jia, Hanxiang; Yang, Xisheng; Guo, Xin; Liu, Jinqiang; Li, Xiaohua (Frontiers in Nutrition, 2023)
Objective To study the value of Onodera's prognostic nutrition index (PNI) in patients with gastric neuroendocrine cancer (G-NEC). Methods The clinical data on 148 cases of G-NEC presented between March 2010 and April 2022 were retrospectively analyzed. The relationship between the clinical characteristics of the patients and PNI was analyzed. Optimal PNI cutoff values for G-NEC prognosis prediction were calculated using the X-tile software. The survival curves were created using the Kaplan-Meier method. A Cox proportional hazards model was also established to identify independent prognostic factors that impact the prognosis of patients with G-NEC.The median overall survival (OS) rate was 30 months (range 6-127 months), and the OS rates at 1, 3 and 5 years were 89.2%, 71.6% and 68.2%, respectively. The mean PNI of the 148 patients before the operation was 49.5±8.0. The mean PNI of patients with anemia (P<0.001) and abnormal carcinoembryonic antigen (P=0.039) was significantly lower than that of patients without such comorbidities. The mean PNI of patients with Stage III tumors (P <0.001) and postoperative complications was significantly lower (P=0.005). PNI optimal cutoff values were 50 (P<0.001). Based on the cut-off value of the PNI, these patients were divided into a PNI-high group (PNI≥50.0, n=77) and a PNI-low group (PNI<50.0, n=71). The PNI-high group had a significantly better 5-years OS rate compared with the PNI-low group (76.6% vs 59.2%， 2 =14.7, P <0. 001). Multivariate analysis demonstrated that PNI and pathological stage were independent prognostic factors for patients with G-NEC. In the subgroup analysis, OS rates were significantly lower in the PNI-low group than in the PNI-high group among patients with stage I and stage III of the disease.The PNI is a simple and useful marker for predicting long-term outcomes in G-NEC patients regardless of tumor stage. Based on our results, we suggest that PNI should be included in routine assessments of patients with G-NEC.